Nurses beliefs on benefits and barriers to physical activity promotion for cancer patients in Hospital Universiti Sains Malaysia - Li, Teh Hui (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Physical activity for most cancer patients still insufficient to obtain health benefits; and adverse effects of cancer-related treatments may reduce regular physical activity. This study aims to determine the nurse’s beliefs on benefits and barriers to physical activity promotion for cancer patients in Hospital USM. A cross-sectional study was conducted on 104 nurses from January 2021 to March 2021 by using a simple random sampling method. A structured self-administered, validated questionnaire was used to collect the data. The data were analyzed using the Statistical Package for Social Science (SPSS) version 26.0 software. The sociodemographic characteristics and level of beliefs on benefit and barriers to physical activity promotion were presented in descriptive statistics and Pearson correlation analysis and independent T test was employed to determine the correlation between nurses’ beliefs on benefits of physical activity promotion and socio-demographic characteristics with a significant level of p ≤.0.05. This study found that most of the participants believe in the benefits of physical activity promotion towards cancer patients such as improving mental health, 80.8% (n=85). Lack of time 30.8% (n=32), patients look tired or not give cooperation 20.2% (n=21) and lack of knowledge 16.3% (n=17) are the most chosen barrier for promoting physical activity among the participants. There was no significant correlation between beliefs on benefits of physical activity promotion with age (p= 0.908), working experiences (p=0.982), type of ward (p=0.666) and the average number of cancer patient care in a week (p=0.144). This study revealed that nurses’ beliefs in the benefits of physical activity promotion towards cancer patients. However, there were barriers to promoting physical activity to cancer patients. Therefore, strengthening the provision of health information about physical activity promotion by designing appropriate strategies and adjustments for healthcare providers including nurses should be promoted.